Religious Communal of Indigenous Peoples in Improving Economy Through Local Wisdom (A Juridical Study on Rural Credit Institution in Bali) - Ibrahim, Johannes; Haykal, Hassanain (Faculty of Law, Hasanuddin University, 2016)
Rural Credit Institution is a financial institution that is specifically located in Pakraman (customary villages) in Bali. The presence of Rural Credit Institution in Bali adjoined to other bank financial institutions such as Commercial Banks and Rural Banks are widespread throughout the province of Bali. Rural Credit Institutions as a financial institution acquire legality under Article 58 of Act No. 7 of 1992 in conjunction with Act No. 10 of 1998 which provides status as Rural Banks. Local wisdom that owned by Rural Credit Institutions, has the scope of business activities, the types of activities and financial transactions are limited in Pakraman as the target area. Customers who save funds or require a loan to be registered as local residents aimed at empowering communities. It is a characteristic of religious communal of Bali’s people for business activities in the village. The uniqueness in the Rural Credit Institutions is the local wisdom of Bali’s people that can be maintained and not be crushed by globalization.